Resisting stigma: the role of online communities in young mothers' successful breastfeeding - Christina Severinsen; Eva Neely; Rochelle Hutson (BMC, 2024)
Abstract Background Breastfeeding initiation and continuation rates are shaped by complex and interrelated determinants across individual, interpersonal, community, organisational, and policy spheres. Young mothers, however, face a double burden of stigma, being perceived as immature and incompetent in their mothering and breastfeeding abilities. In this study, we aimed to understand the experiences of young mothers who exclusively breastfed for six months and beyond and explore their experiences of stigma and active resistance through social media. Methods In 2020, in-depth telephone interviews about breastfeeding experiences were conducted with 44 young mothers under age 25 in Aotearoa New Zealand who breastfed for six months or longer. Participants were recruited via social media. Interviews were audio-recorded, transcribed and analysed thematically. Results Analysis yielded four themes on young mothers' negotiation of breastfeeding and support. The first three themes revealed young mothers' encounters with socio-cultural contexts. They faced negative judgments about maturity and competence, adverse guidance to supplement or cease breastfeeding, and an undermining of their breastfeeding efforts. The fourth theme showed how young mothers sought alternative support in online environments to avoid negative interactions. Online spaces provided anonymity, convenience, experiential knowledge and social connections with shared values. This facilitated identity strengthening, empowerment and stigma resistance. Conclusion Our research highlights the importance of online communities as a tool for young mothers to navigate and resist the societal stigmas surrounding breastfeeding. Online spaces can provide a unique structure that can help counteract the adverse effects of social and historical determinants on breastfeeding rates by fostering a sense of inclusion and support. These findings have implications for the development of breastfeeding promotion strategies for young mothers and highlight the potential of peer support in counteracting the negative impacts of stigma. The research also sheds light on the experiences of young mothers within the health professional relationship and the effects of stigma and cultural health capital on their engagement and withdrawal from services. Further research should examine how sociocultural barriers to breastfeeding stigmatise and marginalise young mothers and continue to reflect on their socio-political and economic positioning and how it can exacerbate inequities.